(untitled) - Eliopulos, Nick (New York, 2023)
"Bobbie is on a mission. She's already survived one encounter with Logan, the jerk who attacked her village and turned her brother into a zombie. And now she won't rest until she stops his evil plan to conquer the Overworld with his zombie horde. But the closer she gets to foiling Logan, the further away she gets from her original goal: finding a cure for her zombie brother. [Meanwhile], Ben is on babysitting duty. Separated from Bobbie, Ben is now in charge of caring for her little brother Johnny and keeping up with his Zombie Obedience Lessons. Lessons that are going well! Johnny doesn't even need his leash anymore, and he hardly tries to eat people at all--unless they really, really deserve it. Logan's abandoned lair is even starting to feel a little like home"--
Keywords: Fantasy; Fiction; Video games; Fiction; Adventure and adventurers; Fiction; Zombies; Fiction; Juvenile fiction; Video games; Adventure stories; Juvenile fiction; Zombies; Juvenile fiction; Minecraft (Game); Minecraft (Game)